دور نظم المعلومات في تطوير و تحسيين الاداء في المؤسسات الصغيرة و المتوسطة دراسة حالة مؤسسة الدهن وحدة سوق اهراس - إيناس راشدي; نبيلة شلغاف (My University, 2021)
This study aims at identifying the contribution of information systems and its role in developing and improving overall performance in small and medium sized ntreprises. The current study has been divided into two chapters. the first one is dealt with the theoretical literature of each of information systems, the overall erformance and the relationship between them. While, the second chapter tackled the field study on the National institute of painting ( ENAP-Souk Ahras ) to est this role based on the dimensions of the balanced scorecard. The analytical descriptive approach was relied upon using some of the scientific research tools, uch as the questionnaire, it was distributed to a sample of forty employees and workers in the entreprise. The finding results of this study confirmed the existence of a relationship for the information systems of the organization under study to improve the overall erformance with an impact and contribution that exceeds the average. Learning and growth ................................................ تهدف هذه الدراسة إلى التعرف على مدى مساهمة نظم المعلومات ودوره في تطوير وتحسين الأداء الكلي في المؤسسات الصغيرة و المتوسطة، قد تم تقسيمها إلى فصلين ، تناولنا في الفصل الأول الأدبيات النظرية لكل من نظم المعلومات والأداء الكلي والعلاقة التي سوق أهراس – لاختبار هذا الدور -ENAP تربطهما، فيما تناول الفصل الثاني الدراسة الميدانية التي أجريت على المؤسسة الوطنية للدهن بالاعتماد على أبعاد بطاقة الأداء المتوازن. وتم الاعتماد على المنهج الوصفي التحليلي باستخدام بعض من أدوات البحث العلمي أهمها الاستبيان الذي وزع على عينة تتكون من 40 موظف وعامل بالمؤسسة. وقد توصلت الدراسة إلى عدد من النتائج أهمها وجود علاقة لنظم المعلومات للمؤسسة محل الدراسة بتحسين الأداء الكلي بأثر ومساهمة تفوق المتوسط، وهو ما يعني أن لنظم المعلومات دور في تحسين الأداء الكلي للمؤسسة محل الدراسة بكل أبعاده، لاسيما البعد المالي والزبائن والعمليات الداخلية ودرجة أقل في بعد التعلم والنمو